Mechanistic Target of Rapamycin Complex 2 Regulation of the Primary Human Trophoblast Cell Transcriptome - Rosario, Fredrick J.; Kelly, Amy Catherine; Gupta, Madhulika B.; Powell, Theresa L.; Cox, Laura; Jansson, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Mechanistic Target of Rapamycin Complex 2 (mTORC2) regulates placental amino acid and folate transport. However, the role of mTORC2 in modulating other placental functions is largely unexplored. We used gene array following silencing of rictor to identify genes regulated by mTORC2 in primary human trophoblast (PHT) cells. Four hundred and nine genes were differentially expressed; 102 genes were down-regulated and 307 up-regulated. Pathway analyses demonstrated that inhibition of mTORC2 resulted in increased expression of genes encoding for pro-inflammatory IL-6, VEGF-A, leptin, and inflammatory signaling (SAPK/JNK). Furthermore, down-regulated genes were functionally enriched in genes involved in angiogenesis (Osteopontin) and multivitamin transport (SLC5A6). The protein expression of leptin, VEGFA, IL-6 was increased and negatively correlated to mTORC2 signaling in human placentas collected from pregnancies complicated by intrauterine growth restriction (IUGR). In contrast, the protein expression of Osteopontin and SLC5A6 was decreased and positively correlated to mTORC2 signaling in human IUGR placentas. In conclusion, mTORC2 signaling regulates trophoblast expression of genes involved in inflammation, micronutrient transport, and angiogenesis, representing novel links between mTOR signaling and multiple placental functions necessary for fetal growth and development.